A Method for Synthesizing Ultra-Large-Scale Clock Trees - Ziheng Li; Benyuan Chen; Wanting Wang; Hui Lv; Qinghua Lv; Jie Chen; Yan Wang; Juan Li; Cheng Zhang (Algorithms)
As integrated circuit technology continues to advance, clock tree synthesis has become increasingly significant in the design of ultra-large-scale integrated circuits. Traditional clock tree synthesis methods often face challenges such as insufficient computational resources and buffer fan-out limitations when dealing with ultra-large-scale clock trees. To address this issue, this paper proposes an improved clock tree synthesis algorithm called incomplete balanced KSR (IB-KSR). Building upon the KSR algorithm, this proposed algorithm efficiently reduces the consumption of computational resources and constrains the fan-out of each buffer by incorporating incomplete minimum spanning tree (IMST) technology and a clustering strategy grounded in Balanced Split. In experiments, the IB-KSR algorithm was compared with the GSR algorithm. The results indicated that IB-KSR reduced the global skew of the clock tree by 43.4% and decreased the average latency by 34.3%. Furthermore, during program execution, IB-KSR maintained low computational resource consumption.